2022
DOI: 10.3390/jcm11154360
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Service-Learning on Physiotherapy Students: Exercise Programs for Patients with Heart Transplantation and Acute Coronary Syndrome—A Randomized Clinical Trial

Abstract: Introduction. Service-learning (SL) seems to be useful for healthcare students. This study aimed at comparing an SL program versus a traditional approach (TA) on moral sensitivity, ethical competences, knowledge, teaching quality, SL participation and performance, and satisfaction in physiotherapy students. Methods. Randomized clinical trial. A total of 32 physiotherapy students were allocated to an SL group (SLG, n = 16), or to a TA group (TAG, n = 16). Participants had to create an exercise program for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…This study found that students perceived the SLC as contributing to the development of their clinical skills, which agrees with research by Heales et al, 27 who investigated factors affecting student satisfaction in an Australian student‐led physiotherapy clinic, and a study conducted with physiotherapy students in a student‐led pro bono clinic in the US 18 . Other studies have supported this finding with objective improvement of clinical performance scores for individual physiotherapy students participating in SLCs 32 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study found that students perceived the SLC as contributing to the development of their clinical skills, which agrees with research by Heales et al, 27 who investigated factors affecting student satisfaction in an Australian student‐led physiotherapy clinic, and a study conducted with physiotherapy students in a student‐led pro bono clinic in the US 18 . Other studies have supported this finding with objective improvement of clinical performance scores for individual physiotherapy students participating in SLCs 32 …”
Section: Discussionsupporting
confidence: 90%
“…18 Other studies have supported this finding with objective improvement of clinical performance scores for individual physiotherapy students participating in SLCs. 32 Students perceived the SLC as contributing to the development of their clinical skills.…”
Section: Enhanced Clinical Skills Developmentmentioning
confidence: 99%
“…Haar and Scanlan (2012) found that students perceived a higher sense of classroom community when instructors facilitate more hands-on learning experiences. Similarly, Marques-Sule et al (2022) found students in a communitybased classroom rated their learning, motivation, and comprehension of course material higher than in a traditional classroom. Research supports the notion that how a student perceives their classroom community matters.…”
mentioning
confidence: 92%